Sistem Pendukung Keputusan Pemilihan Paket Pernikahan Berbasis Web Dengan Menggunakan Metode Saw (Simple Additive Weighting) Studi Kasus Di Joglomas Solo - Pramudita, Intan, Nurgiyatna, ST., MSc., PhD (2017)
Marriage is the most awaited moment of every person. The bride will prepare something special on her wedding day, especially when execute a wedding party. But, The bride not easy to prepare wedding party. The bride should prepare a series of event and event details are complete. So, The bride need services Wedding Organizer which can provide some wedding packages with different prices and different facilities. Customer have a choice of wedding packages to make the customer the difficulty of choosing a wedding packages. This system can facilities the selection of wedding package without need to meet in person. Decision-making system is made using Simple Additive weighting method (SAW) and made with php programming language, HTML and mySQL database. SAW method used to find the optimal alternative from a number of alternatives. Customers can choose the desired packages based criteria catering, documentation, decorations and bridal makeup, the number of guests and the price of package which is determined by the user based on the level of interest. The results of this system is to show the wedding package based on the rating of wedding packages that can be ordered by customers. Customers can choose wedding packages by completing the form package selection.